Kimura Disease – A Rare Cause of Chronic Swelling and Inflammation - Patta, Keerthana; Barphe, Priyanka; Dahiphale, Devidas B; Joshi, Saurabh (Journal of Neonatal Surgery, 2025)
Kimura Disease (KD) is a rare, benign chronic inflammatory condition characterized by painless subcutaneous nodules, lymphadenopathy, eosinophilia, and elevated serum IgE levels. This report describes a 35-year-old female with a painless left-sided head and neck mass. Diagnosis was confirmed by clinical, radiological, and histopathological evaluation. Due to its overlapping features with malignancy and other inflammatory conditions, timely recognition of KD is essential for proper management.